Characterization of MXene as a Cancer Photothermal Agent Under Physiological Conditions - Shurbaji, Samar; Manaph, Nimshitha P. Abdul; Ltaief, Samia M.; Al-Shammari, Abeer R.; Elzatahry, Ahmed; Yalcin, Huseyin C. (Frontiers in Nanotechnology, 2021)
A growing interest has recently emerged for the use of nanomaterials in medical applications. Nanomaterials, such as MXene has unique properties due to its 2D ultrathin structure, which is potentially useful in cancer photothermal therapy. To be most effective, photothermal agents need to be internalized by the cancer cells. In this study, MXene was fabricated using chemical reactions and tested as a photothermal agent on MDA-231 breast cancer cells under static and physiological conditions. Fluid shear stress (~ 0.1 Dyn/cm2) was applied using a perfusion system in order to mimic the physiological tumor microenvironment. The uptake of MXene was analyzed under fluid flow compared to static culture using confocal microscopy, scanning electron microscopy (SEM), energy dispersive spectrometer (EDS) and transmission electron microscopy (TEM). Furthermore, a viability assay was used to assess cells survival after exposing the treated cells to photothermal laser at different power densities and durations. We showed that when incubated with cancer cells, 2D MXene nanoparticles were successfully internalized into the cells resulting in increased intracellular temperatures when exposed to NIR laser. Interestingly, dynamic culture alone did not result in a significant increase in uptake suggesting the need of surface modifications for enhanced cellular uptake under shear stress.